The Sporting Sense of Life in Ortega y Gasset’s Ratiovitalistic Hermeneutics - Conill Sancho, Jesús (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
This work aims to show, in the first place, that the ratiovitalism of Jose Ortega y Gasset is one of the possible lines of the hermeneutics transformation process of contemporary thinking. Nietzsche’s hermeneutical mark on the development of Ortega’s thinking is clear in some very relevant aspects, such as the importance of the body and the innovative notion of life, both of which are decisive issues to understand sport. Secondly, an attempt is made to tap into the rich reflections of Ortega y Gasset on sport, which have a considerable impact on the entire human life, based on the claim of a notion of living body (Leib) and of a new notion of life. Sport forms part of a vital horizon that is not reduced by the narrow utilitarian perspective, but which announces the superior form of human existence, opening up to a festival and creative meaning of life. This requires a discipline that is not merely satisfied with correctly complying with some standards, but which encourages indefinite improvement. The attribute of sport is creative vitality, a new way of understanding life. Because, based on this new vital perspective, homo oeconomicus can no longer be used as a model, but rather, the vital phenomenon understood in a sporting manner is festival, joyful, creative, agonal and Olympic, freely vigorous, a meaningful source of energy. Life is, in principle, creation, a creative experiment, as in the Nietzschean conception.